The Effect of Different Azolla microphylla Biomass on Chemical of Peat Water Parameters on Maintenance Media of Siam Catfish (Pangasius hypophthalmus) - Vadissa Putri Utami; Saberina Hasibuan; Syafriadiman Syafriadiman (Jurnal Akuakultur SEBATIN, 2022)
Peat water has potential for the development of fishery commodities and a strategy is needed through a biological approach by utilizing the Siamese catfish which can adapt to peat water and Azolla microphylla which can improve the quality of peat water. For 28 days in August-September 2021 this research was carried out at the Experimental Pool and Marine Chemistry Laboratory, Faculty of Fisheries and Marine Affairs, Riau University. The purpose of this study was to determine the effect of Azolla microphylla biomass and to obtain the best biomass in improving the chemical parameters of peat water in Siamese catfish (Pangasius hypophthalmus) rearing media. This research method uses a completely randomized design (CRD) with 1 factor with 4 treatment levels and 3 replications. The treatment in this study was the administration of different Azolla microphylla biomass, namely Am0 (Control), Am1 (20 g/m2), Am2 (40 g/m2), and Am3 (60 g/m2) with several parameters measured (DO, nitrate, orthophosphates, spesific growth rate and feed efficiency). The results showed that the best treatment was Am3 (60 g/m2) was able to improve the quality of peat water chemical parameters of Siamese catfish rearing media such as improving the dissloved oxygen value (3.30 mg/l to 7.66 mg/l), increasing the nitrate content water (0.43 ppm to 16.86 ppm) and increased orthophosphate content of water (0.64 ppm to 3.52 ppm). Increase the spesific growth rate of Siamese catfish by 3.89% and increase the feed efficiency of Siamese catfish by 88.01%.